New regionalism or no regionalism? emerging regionalism in the Black Sea area - Ivan, Ruxandra (International political economy of new regionalisms series, 2012)
The first part of the book places the Black Sea problematique in a wider historical and spatial context. The authors then take a closer look at the region and examine further the structure of the Black Sea area. They offer a perspective on smaller actors with great ambitions, such as Azerbaijan and Romania, and go on to make a comparison between the emerging regionalism in the Black Sea area and regionalisms in other parts of the world